A new model for Trypanosoma cruzi heme homeostasis depends on modulation of TcHTE protein expression - Pagura, Lucas (2020)
Fil: Fil: Pagura, Lucas. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.